Gene expression imputation identifies candidate genes and susceptibility loci associated with cutaneous squamous cell carcinoma - Nilah M. Ioannidis (Nature Portfolio, 2018)
Genetic loci linked to susceptibility for the common skin cancer cutaneous squamous cell carcinoma (cSCC) have been identified by genome wide association studies (GWAS). Here, the authors impute gene expression levels from GWAS data to perform a transcriptome wide association study (TWAS), identifying five novel genetic loci linked to cSCC susceptibility.